Pyruvate prevents the onset of the cachectic features and metabolic alterations in myotubes downregulating STAT3 signaling. Issue 11 (28th October 2022) - Mannelli, Michele; Gamberi, Tania; Garella, Rachele; Magherini, Francesca; Squecco, Roberta; Fiaschi, Tania
Abstract: Cachexia is a systemic disease associated with several pathologies, including cancer, that leads to excessive weight loss due to enhanced protein degradation. Previously, we showed that cachectic features in myotubes are provoked by a metabolic shift toward lactic fermentation. Our previous results led us to hyphotesise that increasing pyruvate concentration could impede the metabolic modifications responsible for induction of cachexia in myotubes. Here, we demonstrated that the addition of sodium pyruvate in conditioned media from CT26 colon cancer cells (CM CT26) prevents the onset of either phenotypic and metabolic cachectic features. Myotubes treated with CM CT26 containing sodium pyruvate show a phenotype similar to the healthy counterpart and display lactate production, oxygen consumption, and pyruvate dehydrogenase activity as control myotubes. The use of the Mitochondrial Pyruvate Carrier inhibitor UK5099, highlights the importance of mitochondrial pyruvate amount in the prevention of cachexia. Indeed, UK5099‐treated myotubes show cachectic features as those observed in myotubes treated with CM CT26. Finally, we found that sodium pyruvate is able to decrease STAT3 phosphorylation level, a signaling pathway involved in the induction of cachexia in myotubes. Collectively, our results show that cachexia in myotubes could be prevented by the utilization of sodium pyruvate which impedes the metabolic modifications responsible for the acquisition of the cachectic features.